Jordan and Lebanon Performance in International Student Assessments - Gajderowicz, Tomasz Janusz (Washington, DC: World Bank, 2022)
This report analyzes the results of various PISA and TIMSS assessment rounds conducted in Jordan and Lebanon to identify trends in achievement, provide insights into factors that contribute to better learning, and allow for cross‑country comparisons. The performance of Jordanian and Lebanese students in reading, mathematics, and science is compared to student achievement in other countries. Comparisons of students’ scores across a range of covariates – such as ability levels, gender, and socioeconomic background – are also presented. The PISA and TIMSS data are also analyzed to understand what factors promote or hamper student educational success in these two countries. The report provides in‑depth analysis beyond simple rankings, analyzing results for different academic subjects, grades, and years. By analyzing various factors associated with learning, especially in specific context of each country, it draws upon a broadened perspective to interpret the results in a real-world context of every day social life.